Dummy-subject man constructions in Thai: A study of forms and functions - Wongwattana, Unchalee Singnoi (Humanities, Arts and Social Sciences Studies, 2025)
The investigation of the dummy subject man, a non-referential pronoun in Thai, has historically received limited scholarly attention, and therefore, lacks a comprehensive analysis encompassing its diverse forms, structures, functions, and their interrelation. This article aims to explore the clausal constructions and the form-function mappings associated with the dummy subject man in Thai. Employing a qualitative approach, this study analyzes a variety of data extracted from contemporary informal and colloquial written narratives. The analysis was conducted within the framework of functional-typological grammar, which elucidates the interaction between grammatical structures and communicative functions. The findings reveal that the dummy subject man occurs across a range of constructions, encompassing both basic and non-basic clause types. Basic clauses exhibit both simple and complex structural patterns. Simple clauses feature intransitive, transitive, and copular verbs. Complex basic clauses manifest as extrapositional pronoun structures. Non-basic clauses include existential-presentational, topic-comment, and cleft constructions. Functionally, basic clauses express lexical-semantic features pertaining to environmental or meteorological phenomena, physical or mental states, activities or actions, spatial distances or related implications, temporal references, and epistemic-valuative-difficulty assessments. Non-basic clauses fulfill discourse-pragmatic functions within two primary domains: information structuring and pragmatic emphasis, such as topic introduction, topic reintroduction, and the presentation of contradictory beliefs. The results of this study not only identify a broader array of structures and functions compared to previous research but also offer a more comprehensive description of clausal constructions featuring the dummy subject man, thereby contributing to a more nuanced understanding of this linguistic phenomenon.